INVESTIGATIONS OF THE BASIC COMPONENT OF FCSR – GENERATOR - Shyrochin, V. P.; Vasyltsov, I. V.; Karpinskij, B. Z. (International Journal of Computing, 2014)
The analysis of the statistical parameters of feedback with carry shift register (FCSR) quasi-random generator has been done. For the investigation were chosen 8 - bits and 9-bits registers. Were investigated the period of the generator and distribution of “one” and “zero” values. Additionally, the generated sequences where tested by NIST STS package.